OP50 Effects of reducing saturated fat, trans fat, salt and added sugar in the brazilian diet: cardiovascular modelling study. (31st August 2015) - Moreira, PVL; Martins, APB; Baraldi, LG; Moubarac, JC; Guzman-Castillo, M; Monteiro, CA; Capewell, S; O'Flaherty, M
Abstract : Background: Sales and consumption of ultra-processed products (UPP) haven risen rapidly in middle-income countries in recent decades. These products are likely to contribute to the growing cardiovascular disease (CVD) burden in these countries because they are heavily marketed and nutritionally imbalanced, being typically high in unhealthy fats, salt and or sugar. In Brazil, ultra-processed products are replacing traditional diets based on fresh and minimally processed food. At the same time, use of salt, oils and sugar in culinary preparations remains high. Our aim is to estimate the likely impact of different dietary changes on preventing cardiovascular deaths by 2030 in Brazil. Methods: We obtained nutritional data from the Brazilian Household Budget Survey 2008/2009. All food items purchased were categorised into 4 food groups according to the Dietary Guidelines for the Brazilian population (2014): G1 fresh and minimally processed food, G2 culinary ingredients (oils, fats, salt and sugar), G3 Processed food and G4 Ultra-processed products . We estimated the energy and nutrient profile of each food group using the Brazilian Table of food Composition (TACO) and the United States Department of Agriculture (USDA). We then used the IMPACT Food Policy model to estimate the reduction in deaths from coronary heart disease and stroke by the year of 2030 to explore two scenarios: Scenario A, if the intakes of saturated fat, trans-fat, salt and added sugar, in Group 2 and Group 3 in Brazil were substantially reduced; and Scenario B, if we halve the amount of the same nutrients in Group 2 and Group 4. Uncertainty was assessed through a probabilistic sensitivity analyses using Monte Carlo simulation. Results: Approximately 390, 368 CVD deaths might be expected in 2030 if current mortality patterns persist. Under scenario A, we estimated that Brazil could experience approximately 140, 580 fewer CVD related deaths in 2030 (64, 700–219, 900) and under scenario B, CVD mortality can be reduced by 19%, resulting in about 31, 900 (13, 450–50, 370) fewer coronary heart disease deaths and 42, 690 (20, 745–66, 375) fewer stroke deaths. Conclusion: This study shows a substantial potential for reducing the cardiovascular disease burden through overall improvements of the Brazilian diet. This might require reducing the penetration of ultra-processed products by means of regulatory policies, as well as comprehensively improving the access and promotion of fresh and minimally processed foods that are part of Brazil traditional diet.